Chaterization of Jatropha curcas Linn. Capsule Husk as feedstock for anaerobic digestion - G Adinurani, Praptiningsih; Hendroko, Roy; Nindita, Anggi; SK, Wahono; Mel, Maizirwan; Sasmito, Andi; Nugroho, Yogo A; Liwang, Tony (Elsevier, 2015)
Jatropha curcas Linn. capsule husk (DH-JcL) is a residu from the manufacture of Crude Jatropha Oil. Biorefinery as part of the “four R’s” was required in DH-JcL for anaerobic digestion feedstock. Analysis result and literature study was concluded that DH-JcL is a material that can be managed as biogas substrate, though the nutrient levels relatively low, and a number of other material such as volatile solid, carbohydrates, cellulose ad lignin was relatively high. The establishment of DH-JcL required twophase digestion as anaerobic microbial pretreatment and pre-acidification. The efficiency of two-phase digestion was able to increase the number of technology i.e. additives; recycling of slurry; variation in operational parameters and fixed film or biofilters utilization